"I do not wish to be valled auctour, but the pore compilatour": The Plight of the Medieval Vernacular Poet - Graham D. Caie (Miscelánea: A Journal of English and American Studies, 2004)
This paper looks at changing attitudes to the role of the vernacular author in the 14th and early 15th century England and Scotland. The title of auctour was previously reserved for the writer of Latin theological works, while the vernacular writer hid behind several guises such as anonymity or the dream vision, and considers himself simply a modest compiler or translator of the work of others. The shift to self-confident author can be traced not only in what they wrote, but in how they presented their work in manuscripts. For that reason I shall be looking at codicological evidence, in particular the writing material, the different scripts, the mise-en-page (which had an interpretative function), glosses and other clues which point to the intrinsic value of the text in its manuscript context. Chaucer, Henryson and Gower are studied in detail, as they went to great lengths to ensure that their work appeared on parchment as authoritative texts, which suggests that, in spite of modesty protests, they considered themselves in their own lifetime to be auctoures.